2011
DOI: 10.1007/s12032-011-9887-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical review and analysis of complications of totally implantable venous access devices for chemotherapy

Abstract: Since the first implant of totally implantable venous access device (TIVAD), performed by Niederhuber and colleague in 1982, the systems have increasingly been used in the field of oncology. We analyzed the clinical reviews and complications of TIVAD in an effort to achieve optimal management. We retrospectively studied 442 cases with TIVAD device at our hospital and we report the results. Four hundred and forty-two TIVAD were placed in the right subclavian vein in 345 cases, the left subclavian vein in 93 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 9 publications
2
32
1
13
Order By: Relevance
“…Por otro lado, las infecciones locales del reservorio (infección del bolsillo subcutáneo) pueden tratarse con antibióticos de carácter local; los 3 casos de infección del bolsillo subcutáneo que se registraron en el estudio de Kim JT et al (21) se curaron con éxito tras la administración de tratamiento local.…”
Section: Nº 46 Abril 2017unclassified
See 2 more Smart Citations
“…Por otro lado, las infecciones locales del reservorio (infección del bolsillo subcutáneo) pueden tratarse con antibióticos de carácter local; los 3 casos de infección del bolsillo subcutáneo que se registraron en el estudio de Kim JT et al (21) se curaron con éxito tras la administración de tratamiento local.…”
Section: Nº 46 Abril 2017unclassified
“…En cuatro estudios sobre este dispositivo, solo había un caso de esta complicación en cada uno (6,12,14,21) . La ruptura del reservorio es dolorosa y crea un hematoma (29) ; en cuanto a la membrana, su rotura es muy poco probable, ya que esta puede ser puncionada alrededor de mil veces sin ser dañada (28) .…”
Section: Fractura Del Catéter Y Embolismo (Síndrome "Pinch-off")unclassified
See 1 more Smart Citation
“…Czę-stość tego powikłania ma bezpośredni związek z doświad-czeniem operatora oraz miejscem dostępu, częściej bowiem mamy z nim do czynienia podczas kaniulacji żyły szyjnej po stronie lewej [16][17][18]. Objawy kliniczne odmy zależą od objętości zajętego miąższu płucnego.…”
Section: Powikłania Ostreunclassified
“…53,54 If there is a doubt of infection in blood or catheter system, serial cultures have to be performed and antibiotic treatment should be started immediately. 12 TIVADs needed to be removed if infectious processes cannot be controlled or relapsed after treatment. Reported rates of infection after TI-VAD implantation ranged from 1.1% to 8.8% 9,19,20,40,43 In the present study, local or blood stream infections were observed in 75 (1.67%) cases on follow-up and 67 (89%) of these patients responded to antibiotic therapy.…”
Section: Late Postprocedural Complicationsmentioning
confidence: 99%